(untitled) (Research, Society and Development, 2021)
Localized adiposity is considered as excessive accumulation of fat in a certain region of the body, which can be treated with dermatofunctional physiotherapy resources. This study aimed to describe, from the literature, which treatments of dermatofunctional physiotherapy obtained positive results for the improvement of localized adiposity and identify the most used treatments for localized adiposity. This is an integrative literature review study, conducted from a survey of scientific articles addressing the treatments of dermatofunctional physiotherapy, through the databases Bireme, Pubmed, Scielo, Lilacs, Medline. The inclusion criteria were articles published between 2016 and 2021, and review articles, books, monographs, events, articles in English and Spanish and articles using resources associated with dermocosmetics were excluded from the study. The results showed that the most widely used treatments, such as radiofrequency and ultrasound were effective for the treatment of localized adiposity.